Epigenetics as an answer to Darwin’s “special difficulty,” Part 2: natural selection of metastable epialleles in honeybee castes - Ruden, Douglas M.; Cingolani, Pablo E.; Sen, Arko; Qu, Wen; Wang, Luan; Senut, Marie-Claude; Garfinkel, Mark D.; Sollars, Vincent E.; Lu, Xiangyi (Frontiers in Genetics, 2015)
In a recent perspective in this journal, Brian R. Herb discussed how epigenetics is a possible mechanism to circumvent Charles Darwin’s “special difficulty” in using natural selection to explain the existence of the sterile-fertile dimorphism in eusocial insects. Darwin’s classic book “On the Origin of Species by Means of Natural Selection” explains how natural selection of the fittest individuals in a population can allow a species to adapt to a novel or changing environment. However, in bees and other eusocial insects, such as ants and termites, there exist two or more castes of genetically similar females, from fertile queens to multiple sub-castes of sterile workers, with vastly different phenotypes, lifespans, and behaviors. This necessitates the selection of groups (or kin) rather than individuals in the evolution of honeybee hives, but group and kin selection theories of evolution are controversial and mechanistically uncertain. Also, group selection would seem to be prohibitively inefficient because the effective population size of a colony is reduced from thousands to a single breeding queen. In this follow-up perspective, we elaborate on possible mechanisms for how a combination of both epigenetics, specifically, the selection of metastable epialleles, and genetics, the selection of mutations generated by the selected metastable epialleles, allows for a combined means for selection amongst the fertile members of a species to increase colony fitness. This “intra-caste evolution” hypothesis is a variation of the epigenetic directed genetic error (EDGE) hypothesis, which proposes that selected metastable epialleles increase genetic variability by directing mutations specifically to the epialleles. Natural selection of random metastable epialleles followed by a second round of natural selection of random mutations generated by the metastable epialleles would allow a way around the small effective population size of eusocial insects.